2019
DOI: 10.1177/0268355519889868
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous reflux patterns in C2 patients: A record of 1196 ultrasound reports

Abstract: Objectives To describe saphenous reflux patterns in patients classified as CEAP C2 by analysis of 2027 vascular ultrasound examination reports. Methods A total of 2027 venous mapping studies were reviewed and 1196 patients classified as CEAP C2 were selected. Patients were classified according to patterns of reflux for the great saphenous vein and for the small saphenous vein, and rates of great saphenous vein and small saphenous vein reflux were analyzed for both sexes. Results The overall prevalence of saphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Many studies of the subject have shown that reflux in superficial or deep veins in a specific general population can be of high prevalence and may be dependent on sex, age, and CEAP clinical stage. 3 , 4 , 7 , 8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies of the subject have shown that reflux in superficial or deep veins in a specific general population can be of high prevalence and may be dependent on sex, age, and CEAP clinical stage. 3 , 4 , 7 , 8…”
Section: Discussionmentioning
confidence: 99%
“…These findings regarding the saphenous vein reflux pattern differ from previous publications in the literature. 7 , 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connection between the anatomical extent of reflux and the progression of primary chronic venous disease has been consistently demonstrated by many studies [ 1 4 ]. Axial reflux and multi-segmental reflux are more prevalent in patients with chronic venous insufficiency (CVI) than in those with less advanced disease.…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…The complete CEAP describes all individual segments but without information regarding which of these segments may be connected. Multiple attempts to create a more detailed classification have resulted in so many classes of reflux that it becomes completely impractical to follow [ 3 , 4 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%